Culture and Religion: The Movement and Thought of Islam Nusantara Nowadays, A Socio-Cultural Reflection - Ahmad Gaus A.F.; Herdi Sahrasad (UIN Maulana Malik Ibrahim Malang, 2019)
The Islamic ummah is usually used to struggling and wrestling with diversity. There are Nusantara Islam, Progressive Islam (Islam Berkemajuan), Wasathiyah Islam or Moderate Islam and a range of other terms such as Transformative Islam, Hadhari Islam, or Progressive Islam which community organizations try to develop Islam or Muslim intellectuals. This paper explores the movement and thought of Islam Nusantara. Since Nahdlatul Ulama (NU) was established, various dynamics of Islamic views have taken place. NU recognizes the diversity of religious opinions in four schools, but puritan Islamic groups feel that only their views are correct, only Islam has the right to enter heaven, only certain books can be read, and only the opinions of the teacher are considered authoritative. They looked enthusiastic and attracted attention of young generation and people who are just passionate about Islam, they are like a meteor that shines brightly, but then fades quickly and finally goes out. The time has proven, movements like that, then grow and disappear and change rapidly. The Nusantara Islam, however, has been down to earth, along with the Progressive Islam have taken steps, both are moving and developing in the future.Umat Islam sudah biasa bergumul dan bergulat dengan keanekaragaman. Ada Islam Nusantara, Islam Berkemajuan (berarti ada Islam yang tidak berkemajuan), ada Islam Wasathiyah atau Islam Moderat (berarti ada Islam yang tidak Moderat), dan sederetan istilah lainnya seperti Islam Transformatif, Islam Hadhari, atau Islam Progresif yang coba dikembangkan oleh organisasi masyarakat Islam atau intelektual Muslim. Artikel ini mengulas pergerakan dan pemikiran Islam Nusantara NU didirikan, beragam dinamika terhadap pandangan keislaman sudah terjadi. NU mengakui keragaman pendapat agama dalam empat mazhab, namun kelompok-kelompok Islam puritan merasa bahwa hanya pandangannya saja yang benar, hanya Islamnya saja yang berhak masuk surga, hanya kitab tertentu yang boleh dibaca, dan hanya pendapat gurunya saja yang dianggap otoritatif. Mereka tampak penuh semangat dan menarik generasi muda atau orang yang baru bersemangat dalam berislam, mereka bagai meteor yang bersinar terang, tapi kemudian cepat pudar dan akhirnya padam. Zaman telah membuktikan, gerakan-gerakan seperti itu tumbuh dan hilang berganti dengan cepat. Islam Nusantara sudah membumi, bersama dengan Islam Berkemajuan, keduanya bergerak dan berkembang ke depan.